Interpretations of virtue (de) in early China - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 2011)
There is wide agreement that “virtue” ﬁnds its closest match inChinese philosophy in the concept of de . As a general concept, deconveys a sense of moral excellence, which ﬁnds expression in con-ceptually distinct virtues such as wisdom and courage. In the Confu-cian tradition it is often maintained that de pertains especially tomoral character or “moral charisma,” which deﬁnes the junzi or“gentleman” ideal.1 In this discussion, without rehearsing the manystudies on the meaning of de or retracing its usages in classical writ-ings,2 I explore how the concept is understood in three recently recov-ered early Chinese texts.